PETAL EPIDERMAL MICROMORPHOLOGY AND ITS TAXONOMIC SIGNIFICANS IN SOME SPECIES OF BIGNONIACEAE FROM EGYPT - Samir S. Teleb; Hussein A. Hussei; Riham Shahee; Marwa M. El-Demerdash (Bulletin of the Iraq Natural History Museum)
Micromorphological characters of petals in 8 genera representing 12 taxa of Bignoniaceae from Egypt were carried out using scanning electron microscopy (SEM) to evaluate their taxonomic importance in petal epidermal micromorphology,includingepidermal cell types (areolate, papillose conical, and areolate mixed with papillose conical), trichome types (non-glandular; funnel shape, flexible and stiff-bristly, and glandular; peltate, capitate, cupular, stipitate, and patelli-form), trichome ornamentation (striate, verucate, and smooth, and stomata on both the abaxial and adaxial surfaces. Stomata are present in all species except Jacaranda acutifoliaHumb. & Bonpl.,1806 andMarkhamia zanzibarica (Bojer ex DC.) K. Schum., 1895. We used the past 4.03 program to performsa statistical analysis on the data set matrices using the unweighted pair group method with arithmetic mean (UPGMA,and a phylogram was produced. Our result showed that the two studied genera of MarkhamiaSeem. ex Baill. ,1888 andTabebuiaGomesexDC., 1838 showed support for the monophyly, however,Tecoma(Juss.,1789) are not monophyletic genera.